Children’s drawing and painting: Entanglements from Maurice Merleau-Ponty (Phenomenology, Humanities and Sciences, 2025)
Our aim consists of relating children’s drawing to issues related to painting, addressed by the history of art, and, especially, by phenomenology. We begin through the criticism of the image’s bad reputation, which dates back to Plato and continues currently. As we move forward in time, we see that the idea of painting as representation emerged and became dominant in the West following the invention, during the Renaissance, of geometric perspective. We show that by understanding perspectivist representation, in its historicity, as a way of expressing our experience of the world and not as the only one, we are freed from the constraints that the perspective used to impose on drawing and painting and we can conceive them as a way of seeing, which does not intend to imitate things, but to express them. Children’s drawing can thus be situated no longer in the order of imitation, but of expression, no longer in the order of representation, but of presentation. As we move from representation to presentation, we abandon, both in painting and in children’s drawing, the theme of imitation, of secondariness, of copying a model, of “coming-after” and children’s drawing appears as a genuine and creative way in which the child expresses the world where he or she lives in.